Performance of Caffeine Content Analysis in Robusta sp and Theobroma cacao L using Iodometry, UV-Vis Spectrophotometry and High Performance Liquid Chromatography - Yeanchon H. Dulanlebit; Nikmans Hattu; Ritti P. Sangadji; Risma Mahulette; Nataniel Kelmanutu; Sandriliati Asari (Chemistry Department, The University of Brawijaya, 2020)
Caffeine is a xanthine alkaloid compound found in Robusta sp and Theobroma cacao L. The caffeine extract was obtained by evaporating CHCl3 using a rotary evaporator and determine its content using iodometry, UV-Vis spectrophotometry and High Performance Liquid Chromatography, then validated by measurement methods. The iodometric caffeine content in Theobroma cacao L is 900 mg/kg while UV-Vis spectrophotometry is 4,000 mg/kg, and for HPLC in Robusta sp is 19,475 mg/kg. The iodometry performance gives the linearity value, R2 of 0.9791. The precision values at 5.0 mg/L and 15.0 mg/L are 4.6% and 8.3%. Accuracy for 5.0; 10.0; and 15.0 mg/L are 106%, 100% and 94% respectively. The performance of UV-Vis spectrophotometry gives linearity value, R2 of 0.9948. The precision value at 1.0 mg/L and 6.0 mg/L gives the variance coefficient value of 4.2% and 1.2%, while the accuracy at 1.0 mg/L and 6.0 mg/L are 99% and 101%.